If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 12 = 8x + -13 Reorder the terms: 12 + 7x = 8x + -13 Reorder the terms: 12 + 7x = -13 + 8x Solving 12 + 7x = -13 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 12 + 7x + -8x = -13 + 8x + -8x Combine like terms: 7x + -8x = -1x 12 + -1x = -13 + 8x + -8x Combine like terms: 8x + -8x = 0 12 + -1x = -13 + 0 12 + -1x = -13 Add '-12' to each side of the equation. 12 + -12 + -1x = -13 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = -13 + -12 -1x = -13 + -12 Combine like terms: -13 + -12 = -25 -1x = -25 Divide each side by '-1'. x = 25 Simplifying x = 25
| -2/5x=6/9 | | 25y^2+15y+2=0 | | 7n-2n=75 | | 13a-8a=-20 | | (9x-55)(3x/55)=90 | | y=2x+6k | | 20+6x=7x-6 | | 3/6x+2=17 | | 4X+10=14X+3+157 | | 6.5(65)= | | x+4/4=n+3 | | 2x^2-3x+196=0 | | (9x-55)(3x^55)=90 | | 17=11-m | | 24+3x=70+2x | | 104/=13/10 | | 7(x+6)=24 | | 13x+10=x | | 8z-7z=-18 | | .5x-3=2x-5 | | 33=3n-1+2n+4 | | a/2+7/4+5 | | 74(x+6)=24 | | (4/7z+2/3z)=13 | | 7(1+5n)+7(1+4n)=13 | | 13x+10= | | y=40x-48/24x+40 | | -10=4-7y/4 | | 6-3v=39 | | 3n+5n=56 | | (4/7z+2/3)=13 | | 3/5x=9/5 |